Diarrhoea-predominant irritable bowel syndrome: an organic disorder with structural abnormalities in the jejunal epithelial barrier. Issue 8 (25th May 2012) - Martínez, Cristina; Lobo, Beatriz; Pigrau, Marc; Ramos, Laura; González-Castro, Ana Maria; Alonso, Carmen; Guilarte, Mar; Guilá, Meritxell; de Torres, Ines; Azpiroz, Fernando; Santos, Javier; Vicario, María
Abstract : Objective: Recently, the authors demonstrated altered gene expression in the jejunal mucosa of diarrhoea-predominant irritable bowel syndrome patients (IBS-D); specifically, the authors showed that genes related to mast cells and the intercellular apical junction complex (AJC) were expressed differently than in healthy subjects. The aim of the authors here was to determine whether these alterations are associated with structural abnormalities in AJC and their relationship with mast cell activation and IBS-D clinical manifestations. Design: A clinical assessment and a jejunal biopsy were obtained in IBS-D patients (n=45) and healthy subjects (n=30). Mucosal mast cell number and activation were determined by quantifying CD117 + cells/hpf and tryptase expression, respectively. Expression and distribution of AJC specific proteins were evaluated by western blot and confocal microscopy. AJC ultrastructure was assessed by transmission electron microscopy. Results: Compared with healthy subjects, IBS-D patients exhibited: (a) increased mast cell counts and activation; (b) increased protein expression of claudin-2, reduced occludin phosphorylation and enhanced redistribution from the membrane to the cytoplasm; and (c) increased myosin kinase expression, reduced myosin phosphatase and, consequently, enhanced phosphorylation of myosin. These molecular alterations were associated with ultrastructural abnormalities at the AJC, specifically, perijunctional cytoskeleton condensation and enlarged apical intercellular distance. Moreover, AJC structural alterations positively correlated both with mast cell activation and clinical symptoms. Conclusion: The jejunal mucosa of IBS-D patients displays disrupted apical junctional complex integrity associated with mast cell activation and clinical manifestations. These results provide evidence for the organic nature of IBS-D, a heretofore model disease of functional gastrointestinal disorders.